Seroprevalence, Prevalence, and Genomic Surveillance: Monitoring the Initial Phases of the SARS-CoV-2 Pandemic in Betim, Brazil - Silva, Ana Valesca Fernandes Gilson; Menezes, Diego; Moreira, Filipe Romero Rebello; Torres, Octávio Alcântara; Fonseca, Paula Luize Camargos; Moreira, Rennan Garcias; Alves, Hugo José; Alves, Vivian Ribeiro; Amaral, Tânia Maria de Resende; Coelho, Adriano Neves; Saraiva Duarte, Júlia Maria; da Rocha, Augusto Viana; et al. (Frontiers in Microbiology, 2022)
The Covid-19 pandemic has created an unprecedented need for epidemiological monitoring using diverse strategies. We conducted a project combining prevalence, seroprevalence, and genomic surveillance approaches to describe the initial pandemic stages in Betim City, Brazil. We collected 3239 subjects in a population-based age-, sex- and neighbourhood-stratified, household, prospective; cross-sectional study divided into three surveys 21 days apart sampling the same geographical area. In the first survey, overall prevalence (participants positive in serological or molecular tests) reached 0.46% (90% CI 0.12% – 0.80%), followed by 2.69% (90% CI 1.88% – 3.49%) in the second survey and 6.67% (90% CI 5.42% - 7.92%) in the third. The underreporting reached 11, 19.6, and 20.4 times in each survey, respectively. We observed increased odds to test positive in females compared to males (OR 1.88 95% CI 1.25 – 2.82), while the single best predictor for positivity was ageusia/ anosmia (OR 8.12, 95% CI 4.72 – 13.98). Thirty-five SARS-CoV-2 genomes were sequenced, of which 18 were classified as lineage B.1.1.28, while 17 were B.1.1.33. Multiple independent viral introductions were observed. Integration of multiple epidemiological strategies was able to describe Covid-19 dispersion in the city adequately. Presented results have helped local government authorities to guide pandemic management.